Some Touching Thoughts and Wishful Thinking - Kleege, Georgina (Disability Studies Quarterly, 2013)
Abstract: I describe a recent touch tour I took at the Museum of Modern Art in New York, and suggest that since sighted visitors do not enjoy the opportunity to touch works of art, museums should collect the observations of blind visitors to expand cultural knowledge by including tactile aesthetics. Key words: blindness, blind museum access, Museum of Modern Art, tactile aesthetics.